Monitoring closed circuit television in Telkom University Landmark Tower using internet of things - Oktavianingrum, Andarista Putri; Azrika, Andi Zhagyta Amalia; Fathurrahman, Muhammad Naufal; Usman, Uke Kurniawan; Hambali, Akhmad (Universitas Telkom, 2025)
This research develops a prototype Closed Circuit Television (CCTV) monitoring system within a university building for remote access using Internet of Things (IoT) technology. Addressing the growing need for security surveillance on campuses, the study uploads processed videos from the Network Video Recorder (NVR) to a Virtual Private Server (VPS), facilitating real-time CCTV monitoring through a website. UiPath, employed for Robotic Process Automation (RPA), automates commands, and the system stores processed video data in its database.The research results indicate that this system is capable of providing effective CCTV monitoring with real-time access through the website. Quantitative data shows user satisfaction survey with a success rate above 40%, answering